The Defibrination Syndrome in Rabbits Following Infusion of Tissue Thromboplastin in the Jugular Vein - Albkechtsen, O. K; Brakman, P; Astrup, T (Thrombosis and Haemostasis, 1970)
The effects of infusion of homologous tissue thromboplastin in the jugular vein of the rabbit was followed by determination of levels of coagulation factors in samples of blood obtained from the systemic arterial circulation by appropriate one-stage methods. The presence of active coagulation components was studied by appropriate two- or three-stage methods. There was marked consumption of coagulation factors, including fibrinogen. No macroscopically visible thrombi were seen in the major vessels of the systemic circulation indicating absence of tissue thromboplastin in the greater circulation. Two-and three-stage tests indicated presence of coagulation enhancing agents different from tissue thromboplastin and of a serum-like nature. Tissue thromboplastin, being bound to particulate matter, was most probably retained in the capillary bed of the lungs, thereby being prevented from appearing in the systemic circulation. The results confirm our previous findings obtained by infusion in the femoral vein. They are discussed and compared with the behavior of infused blood or tissue thromboplastin reported by other authors. Discrepancies in reported data could be traced to differences in sites of infusion or of collection of samples of blood. Changes in plasminogen concentration or in plasma euglobulin fibrinolytic activity on normal and heated fibrin plates were slight.